Effect of birth plan education on anxiety levels among third-trimester pregnant women prior to childbirth: A one-group pretest–posttest study - Heni Fauziah; Fijri Rachmawati; Neneng Siti Lathifah (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Anxiety during the third trimester of pregnancy is a common psychological condition that may adversely affect maternal and fetal outcomes, including prolonged labor, increased obstetric complications, and negative birth experiences. Birth Plan education is a woman-centered educational intervention designed to improve childbirth preparedness, enhance communication with healthcare providers, and reduce maternal anxiety. Purpose: To examine the effect of Birth Plan education on anxiety levels among third-trimester pregnant women prior to childbirth. Method: A pre-experimental study with a one-group pretest–posttest design was conducted among 30 third-trimester pregnant women at the Independent Midwifery Practice (PMB) of Febi Yulistia, Bandar Lampung, Indonesia, between April and May 2025. Participants were recruited using total sampling. Anxiety levels were assessed before and after a 45-minute Birth Plan education session using the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. Results: Before the intervention, the majority of participants experienced moderate anxiety (53.3%), with a mean anxiety score of 18.73 ± 4.36. Following Birth Plan education, most participants reported no anxiety (60.0%), and the mean anxiety score significantly decreased to 11.67 ± 4.55. The Wilcoxon signed-rank test demonstrated a statistically significant reduction in anxiety levels after the intervention (p < 0.001). Conclusion: Birth Plan education effectively reduced anxiety levels among third-trimester pregnant women. Integrating Birth Plan education into routine antenatal care may enhance maternal psychological preparedness for childbirth and contribute to improving maternal health outcomes.